Model Konsep Pengembangan Human Capital dengan Etos Kerja sebagai Variabel Intervaning Menuju Peningkatan Organizational Citizenship Behavior (OCB) dalam Perspektif Hukum Islam - Edwin Hadiyan; Faisal Faisal (Mutawasith: Jurnal Hukum Islam, 2021)
Human resources who have a creative spirit and always develop a positive attitude will improve their performance according to the expectations of the organization. Citizenship behavior will be discussed in the organizational dimension of OCB, human capital development by involving elements of creativity and organizational culture development will increase OCB. The positive behavior of employees is able to support the performance of organizational development for the better. The basic concepts of Islam are faith, Islam and Ihsan. The perfection of Islam can only be built and enforced through these three concepts. The role of Islamic work ethic as an intervaning variable will greatly affect human capital and OCB development. This study uses a quantitative type, the aim is to determine the magnitude of the influence of human resource development, religiosity, on employee performance with job satisfaction as an intervening variable. Data were collected by distributing questionnaires to 100 employees using purposive sampling method to determine respondents' responses to existing variables. The analysis was carried out using the method of Structural Equation Modeling (SEM) based on partial least squares (PLS).